Examining Factory Process Safety Management Systems And Studying Lean Improvement Methods - Bunphot Tepparit; Nanthawan Am-Eam; Kulwarun Warunsin (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
Many factories have set up a safety management system (PSM), and there is an increasing rate of safety management systems. This is increasingly in line with the development of industrial plants. External and internal inspection of security management processes are the core of Process Safety Management (PSM) and are an essential opportunity to improve operational solutions. The problems of security inspection arise due to unclear and unplanned inspection issues, resulting in unsystematic monitoring of factual information and opinions and loss of opportunities to achieve goals throughout the organization. This research aims to improve the inspection process by using computer software technology in auditing. After improving the process according to the Lean Process Management (ECRS) concept to reduce waste, the workflow was reduced by 40.74%, and 60% efficiency was increased. In addition, the assessment results from a sample of PSM auditors showed 93.4% satisfaction as the most appropriate. Therefore, this study demonstrated the potential and benefits of implementing the Process Safety Management System (PSM) audit program and applying Lean theory to improve auditing, which can be used as an essential reference for future research and program development.